Bioinspired Mechanically Interlocking Structures. Issue 3 (27th September 2020) - Zhu, Ming; Zhang, Feilong; Chen, Xiaodong
Abstract : Mechanically interlocking structures at various interfaces in nature have been observed for a long time, and their underlying interacting mechanisms have been deeply investigated. Through material and structural engineering, bioinspired interlocking structures were exploited to gain desirable functionalities with specific interfacial properties, aiming for practical applications in modern electronics. Herein, these bioinspired interlocks are summarized and classified into static and regulable categories according to their engineered functionalities. Static interlocks enhance the interfacial strength, while regulable interlocks further facilitate tunable and reversible attachment or stimuli–responsive ability. Various biomimetic interlocking structures with desirable features offered by static and regulable interlocks show great potential in the application scope of skin‐interfaced electronics, bioinspired adhesives, and stretchable electronic skins. Nevertheless, further exploration and thorough comprehension of mechanisms of natural interlocks are required to utilize each unique interlocking structure for a specific application scenario. With the advancement in materials engineering, functionality‐oriented interlocking structures will be developed toward practical applications in integrated healthcare electronics. Abstract : Mechanically interlocking structures at various interfaces in nature have been observed for a long time. Through material and structural engineering, bioinspired interlocking structures have been exploited to gain desirable functionalities, reaching toward practical applications. Herein, bioinspired natural interlocks are summarized and classified into static and regulable categories according to their oriented functionalities toward advanced applications in integrated healthcare electronics.